Review of Seventh Series FPGA Xilinx - Свид, І. В.; Мальцев, О. С.; Сайківська, Л. Ф.; Зубков, О. В. (NURE, MC&FPGA, 2019)
The work of the Xilinx FPGA of the 7th series was reviewed, as well as a comparative description of its families.
Keywords: FPGA; DSP; XADC; Xilinx; Spartan-7; Artix-7; Kintex-7; Virtex-7